In Vitro Investigations of miR-33a Expression in Estrogen Receptor-Targeting Therapies in Breast Cancer Cells - KILBAŞ, PELİN ÖZFİLİZ; SÖNMEZ, ÖZLEM; Çoker-Gürkan, Ajda; Palavan-Ünsal, Narcin; Uysal-Onganer, Pınar; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (MDPI, 2021)
Simple Summary: Altered metabolic pathways determine the aggressivity of breast cancer cells. To highlight the potential markers gains importance to understand early molecular signatures of disease. microRNAs are the small non-coding RNAs found in different biological samples. Due to the dysregulation of metabolic pathways, the expression and secretion of microRNAs are modulated. (1) Background: Increased fatty acid synthesis leads to the aggressive phenotype of breast cancer and renders efficiency of therapeutics. Regulatory microRNAs (miRNAs) on lipid biosynthesis pathways as miR-33a have potential to clarify the exact mechanism. (2) Methods: We determined miR-33a expression levels following exposure of MCF-7 and MDA-MB-231 breast cancer cells to estrogen receptor (ER) activator (estradiol-17 beta, E2) or anti-estrogens (ICI 182,780, Fulvestrant, FUL) at non-cytotoxic concentrations. We related miR-33a expression levels in the cells to cellular lipid biosynthesis-related pathways through immunoblotting. (3) Results: miR-33a mimic treatment led to significantly downregulation of fatty acid synthase (FASN) in MCF-7 cells but not in MDA-MB-231 cells in the presence of estradiol-17 beta (E2) or Fulvestrant (FUL). In contrast to the miR-33a inhibitor effect, miR-33a mimic co-transfection with E2 or FUL led to diminished AMP-activated protein kinase a (AMPKa) activity in MCF-7 cells. E2 increases FASN levels in MDA-MB-231 cells regardless of miR-33a cellular levels. miR-33a inhibitor co-treatment suppressed E2-mediated AMPKa activity in MDA-MB-231 cells. (4) Conclusions: The cellular expression levels of miR-33a are critical to understanding differential responses which include cellular energy sensors such as AMPKa activation status in breast cancer cells.
Keywords: Estrogen; Breast Cancer; miR-33a; Adipogenesis; FASN; Fulvestrant